2002
DOI: 10.1097/01.asn.0000027354.12330.f4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence of Two Distinct Functions for the Inducible NO Synthase in the Rat Kidney

Abstract: Abstract. The functional role of the NO synthase (NOS) isoforms in the normal or diseased kidney is uncertain. This study examined the renal expression of the endothelial (eNOS), neuronal (nNOS), and inducible (iNOS) isoforms by both immunohistochemistry and Western blot analyses in shamoperated rats (S) and in rats subjected to 5/6 nephrectomy (Nx). Primary antibodies from two different sources were used to detect iNOS. Additional S and Nx rats were chronically treated with aminoguanidine (AG), a selective iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
6
19
1
3
Order By: Relevance
“…The protein abundance of eNOS seems to be variable in models of renal mass reduction associated with significant injury, and in- creases (20), decreases (15,18,19), and no change (1) (this study) have been reported. The reasons for these differences are unclear but may be related to differences in rat strain, extent of renal mass reduction, time after renal mass reduction, or ablation versus A/I treatment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The protein abundance of eNOS seems to be variable in models of renal mass reduction associated with significant injury, and in- creases (20), decreases (15,18,19), and no change (1) (this study) have been reported. The reasons for these differences are unclear but may be related to differences in rat strain, extent of renal mass reduction, time after renal mass reduction, or ablation versus A/I treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Studies using renal mass reduction have also demonstrated decreased nNOS, inducible NOS, and eNOS levels in the remnant kidney (15,16,18,19). Our laboratory recently demonstrated that renal nNOS levels were consistently reduced in several models of CRD in SD rats.…”
Section: Discussionmentioning
confidence: 81%
“…These disparate findings are not completely incompatible, since iNOS in one and same organ or tissue may exist in distinct fractions, e.g. in the kidney where interstitial iNOS differs from tubular iNOS in the inhibition by aminoguanidine [37]. An added complication is that the expression of iNOS gene, like other genes induced in inflammatory responses, may vary according to the cell type and the stimulus, and thus may be upregulated [20] or downregulated [38] by HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently shown that completely different staining patterns were found using 2 different, commercially available anti-iNOS antibodies. 17 In addition, iNOS expressions was increased in the CK. Compensatory changes in the CK in UUO have been reported, 18 and the up-regulation of NOS and subsequent NO production may be involved in these changes.…”
Section: Methodsmentioning
confidence: 96%